Empowerment of Semampir Village in Kediri City Through Optimization of Traditional Sports Ecoedu Towards an Ecoedu Sport Tourism Destination - Nur Ahmad Muharram; Agung Pratama, Budiman; Prasetiyo Herpandika, Reo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Semampir Village has great potential to be developed as a tourist destination for Ecoedu Sport Tourism because of the pristine natural beauty of its countryside. One of the attractions is a playground called riverside Semampir Village, Kediri City. Apart from its beautiful nature, Semampir Village is also rich in art and culture spread across various hamlets, and has traditional games which are part of local wisdom. The aim of this service activity is to encourage the development of Semampir Village as an Ecoedu Sport Tourism destination by optimizing the potential of traditional sports. The methods used in this service are Service Learning and CIPP, which aim to help partners solve problems faced in the tourism sector. Some of the activities that have been carried out include: 1) Literature study regarding traditional sports as part of Ecoedu Sport Tourism based on SWOT analysis, 2) Reintroduction of traditional games to children in Semampir Village, 3) Socialization and training of traditional sports, and 4) Focus group discussion (FGD) about tourist villages. The results achieved include: 1) Preparation of a joint commitment working paper between Semampir Village stakeholders as well as the results of the village SWOT analysis, and 2) Increasing the capacity of Pokdarwis and tourism managers in recognizing various types of traditional sports. The follow-up to this service will focus on strengthening the Semampir Village tourism promotion sector